Quality assessment of bituminous binders based on the viscoelastic properties: Polish experience - Radziszewski, Piotr; Kowalski, Karol J. (Journal of Civil Engineering and Management, 2014)
Construction of modern and durable bituminous pavements requires high quality bituminous binder, aggregates and additives. The main objective of this paper was to analyse and compare viscoelastic properties of unmodified and polymer modified bitumens produced in Poland, Europe, in order to assess their quality. In this paper there are presented results of bituminous binder European classification tests (penetration, softening point and Fraass breaking point) as well as rheological test results conducted over a wide range of temperatures. In addition, image analysis of the microstructure of selected polymer modified bitumens is also presented. Based on the analysis it was concluded that although bituminous binders complies with European specification requirements, they are significantly different in terms of their rheological properties. It was found that regardless of binder producer, bituminous binder within the same hardness group exhibit different low and high temperature properties.